2023
DOI: 10.3390/ijms24031900
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potent Zika Virus NS5 RNA-Dependent RNA Polymerase Inhibitors Combining Virtual Screening and Biological Assays

Abstract: The Zika virus (ZIKV) epidemic poses a significant threat to human health globally. Thus, there is an urgent need for developing effective anti-ZIKV agents. ZIKV non-structural protein 5 RNA-dependent RNA polymerase (RdRp), a viral enzyme for viral replication, has been considered an attractive drug target. In this work, we screened an anti-infection compound library and a natural product library by virtual screening to identify potential candidates targeting RdRp. Then, five selected candidates were further a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…They found that in ZIKV-infected Vero cells, it had an EC 50 value of 49.55 μM and a CC 50 value of 4,000 μM. Chen et al conducted a virtual screening of anti-infective drugs using a natural product library to identify possible RdRp inhibitors ( Chen et al, 2023 ). Further RdRp enzymatic testing, cytotoxicity assessment, and SPR testing determined that Compound 78 (Ketoconazole) effectively inhibited RdRp activity (IC 50 = 4.29 µM) with an EC 50 value of 0.59 µM in a Huh-7 cell model.…”
Section: Zikv Drugsmentioning
confidence: 99%
“…They found that in ZIKV-infected Vero cells, it had an EC 50 value of 49.55 μM and a CC 50 value of 4,000 μM. Chen et al conducted a virtual screening of anti-infective drugs using a natural product library to identify possible RdRp inhibitors ( Chen et al, 2023 ). Further RdRp enzymatic testing, cytotoxicity assessment, and SPR testing determined that Compound 78 (Ketoconazole) effectively inhibited RdRp activity (IC 50 = 4.29 µM) with an EC 50 value of 0.59 µM in a Huh-7 cell model.…”
Section: Zikv Drugsmentioning
confidence: 99%
“…Coronavirus (COVID-19) is a positive, single-stranded RNA that induces severe respiratory infections (SARS-CoV-2), which emerged in late 2019 from Wuhan, China. , As a result of its widespread occurrence and rapid human transmission leading to loss of lives, the World Health Organization (WHO) officially declared it a pandemic. As of April 6, 2023, human SARS-CoV-2 viral transmission has reached 762,201,169 cases and 6,893,190 confirmed deaths across the globe . Additionally, the mutated RNA of SARS-CoV-2 has given rise to resistant and virulent novel variants, imposing a significant burden on the scientific community to develop successful medicines and vaccines. Although existing vaccines and drugs can reduce the severity of the disease, there is some cause for concern about the efficacy of vaccines in the context of increasing numbers of mutations. Despite many possible targets, the RdRp (nsp12) complex is responsible for RNA replication and represents an ideal target for innovative RdRp inhibitors. The use of RdRp has been a crucial strategy for treating several viral infections, including hepatitis C (HCV), , dengue, , zika, , influenza, , etc. Based on structural disparities and the mode of action, RdRp inhibitors can be categorized into two groups: nucleoside/nucleotide analogues (NAs) and non-nucleoside/nucleotide analogues (NNAs). , These nucleoside analogues are transformed into active nucleoside triphosphates by cellular enzymes, which deceive and trick SARS-CoV-2 RdRp and then are incorporated into the strand to stop viral replication. ,, Some commonly used clinically approved repurposed SARS-CoV-2 nucleoside RdRp inhibitors used to decrease morbidity and mortality are Remdesivir and Molnupiravir. , Other nucleoside RdRp inhibitors include Favipiravir, Galidesivir, Ribavirin, Sofosbuvir, Azvudine, and Taroxaz-26. ,, Meanwhile, non-nucleoside analogues (NNAs) disrupt viral replication by directly binding to the active site of RdRp, which is one of their benefits over NAs. , To date, only a few RdRp NNAs have been reported .…”
Section: Introductionmentioning
confidence: 99%
“… 11 14 Despite many possible targets, the RdRp (nsp12) complex is responsible for RNA replication and represents an ideal target for innovative RdRp inhibitors. 15 17 The use of RdRp has been a crucial strategy for treating several viral infections, including hepatitis C (HCV), 18 , 19 dengue, 20 , 21 zika, 20 , 22 influenza, 23 , 24 etc. Based on structural disparities and the mode of action, RdRp inhibitors can be categorized into two groups: nucleoside/nucleotide analogues (NAs) and non-nucleoside/nucleotide analogues (NNAs).…”
Section: Introductionmentioning
confidence: 99%
“…The genome of Zika, like other flaviviruses, has two non-coding regions, 3'UTR and 5'UTR, which are essential for the initiation of negative strand RNA synthesis to occur in the host cell (Markoff, 2003). The remainder of the genome encodes a single precursor polyprotein, which must be processed by cellular and viral proteases to form all structural (C, M and E) and non-structural virus proteins (NS1, NS2a, NS2B, NS3, NS4A, 2K, NS4B and NS5) (Zhang et al, 2003, Lee & Shin, 2019, Labib & Chigbu, 2022, Chen et al, 2023.…”
Section: Introductionmentioning
confidence: 99%